Utilization of free maternity services among mothers aged 18-49 years in Nakuru County, Kenya - Najoli, Priscilla J.; Kirui, Joyce; Wanjau, Grace; Otieno, George; Yoos, Alison; Biketi, George (International Journal Of Community Medicine And Public Health, 2021)
Background: In Kenya, the hope of free maternity services (FMS) is to increase the demand for maternity health care services offered by certified health professionals. Thus, this study aimed to determine and understand the utilization level of FMS among mothers aged 18-49 years living in Naivasha Sub-County, Kenya. Methods: A mixed-methods approach collected quantitative and qualitative data through structured questionnaires, health records reviews, focus group discussions, and key informant interviews. The quantitative and qualitative data were analyzed by use of Statistical package for social sciences (SPSS) 20 and content analysis, respectively. The quantitative data results were further subjected to multiple regression analysis. Results: The findings showed that over 80% utilized antenatal care, facility deliveries and postnatal care, but 68% of respondents used family planning. The mothers were found active in their first, second and third pregnancies in utilizing FMS, followed by a sudden decline. The mothers preferred the public health facilities to the private, mission and Non-Governmental Organizations (NGOs). The significant findings influencing the utilization of FMS among the mothers were age (p=0.004), the number of children (p=0.000), age at first birth (p=0.025), household income (p=0.008) and residential area (p=000). The mothers’ level of knowledge on FMS had an average score of 80%, obtained by use of the Linkert scale. The radio, television, health facility and community sources were significant with (p=0.000). Conclusions: The decision-makers consider age, the number of children, age at first birth, household income and residential area in the formulation of FMS policies. Further, utilize relevant sources of information on FMS in the community.